Advances with glucocorticoids in the treatment of asthma: state of the art. (11th December 2020) - Ora, Josuel; Calzetta, Luigino; Matera, Maria Gabriella; Cazzola, Mario; Rogliani, Paola
ABSTRACT: Introduction: Asthma is one of the most frequent chronic diseases all over the world. Glucocorticoids (GCs), both inhaled (ICSs) and oral (OCSs), are the most effective treatment in asthma because they control symptoms and prevent exacerbations. Areas covered: The present article reviews the new therapeutic indications of GCs for the treatment of asthma and focuses on new molecules and safety issues. Expert opinion: Most patients with asthma benefit from corticosteroid-based treatments. Side effects are mainly due to prolonged use of oral GCs, while they are minor with inhaled GCs. Interesting insights come from the new ICSs, which are characterized by lower oral bioavailability and higher lipophilicity and are more effective with less side effects. Recent trials have shown the efficacy of early use of ICSs in mild asthma. Furthermore, the possibility to prescribe targeted therapies using specific biomarkers in steroid-sensitive asthma can reduce doses and duration of treatment, while biological agents should be reserved for non-responding patients. All this evidence confirm the need to continue on the path toward precision medicine, in which the treatments are based on clinical and molecular traits.